Exponential Time Differencing-Padé Finite Element Method for Nonlinear Convection-Diffusion-Reaction Equations with Time Constant Delay (Journal of Computational Mathematics, 2023)
In this paper, ETD3-Pad\u00e9 and ETD4-Pad\u00e9 Galerkin finite element methods are proposed and analyzed for nonlinear delayed convection-diffusion-reaction equations with Dirichlet boundary conditions. An ETD-based RK is used for time integration of the corresponding equation. To overcome a well-known difficulty of numerical instability associated with the computation of the exponential operator, the Pad\u00e9 approach is used for such an exponential operator approximation, which in turn leads to the corresponding ETD-Pad\u00e9 schemes. An unconditional $L^2$ numerical stability is proved for the proposed numerical schemes, under a global Lipshitz continuity assumption. In addition, optimal rate error estimates are provided, which gives the convergence order of $O(k^{3}+h^{r})$ (ETD3-Pad\u00e9) or $O(k^{4}+h^{r})$ (ETD4-Pad\u00e9) in the $L^2$ norm, respectively. Numerical experiments are presented to demonstrate the robustness of the proposed numerical schemes.